2015
DOI: 10.1136/acupmed-2013-010441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture at Ht7 on Heart Rate Variability: An Exploratory Study

Abstract: Objective To explore the effect of acupuncture at HT7 on heart rate variability (HRV) in healthy volunteers. Methods 120 subjects were divided into four groups using a random number table. The following groups of acupuncture interventions were used: HT7 verum acupuncture; HT7 nonpenetrating sham acupuncture; acupuncture at a sham point; and no acupuncture. HRV was recorded 10 min before, during and after each stimulation using an Actiheart ECG recorder. Results The HT7 verum acupuncture group had higher very-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Changes in the activity of the autonomic nervous system after the application of certain physiotherapy techniques have been reported by some authors, especially invasive techniques such as percutaneous needle electrolysis and acupuncture [15][16][17][18][19], but also electrotherapy techniques such as interferential currents [20]. Mild vagal reactions have also been observed during the application of noninvasive physiotherapy techniques, such as craniosacral therapy [21] and massage [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the activity of the autonomic nervous system after the application of certain physiotherapy techniques have been reported by some authors, especially invasive techniques such as percutaneous needle electrolysis and acupuncture [15][16][17][18][19], but also electrotherapy techniques such as interferential currents [20]. Mild vagal reactions have also been observed during the application of noninvasive physiotherapy techniques, such as craniosacral therapy [21] and massage [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…LI11 and SP10 are used frequently to treat itch in clinical and experimental studies (Pfab et al, 2005, 2010, 2011, 2012a). To induce activation of the PNS, HT7 (Huang et al, 2015) and PC6 (Huang et al, 2005; Li et al, 2005) were chosen. ST36 is the most frequently used acupoint for immune regulation and anti-inflammatory effects, and reducing SNS (Michikami et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies suggest that acupuncture influences ANS functions such as blood pressure, skin conductance, skin temperature, heart rate, and heart rate variability (HRV) (Malliani et al, 1991; Lee et al, 2010; Chung et al, 2014). Studies found that press needle stimulation induces alterations in vagal function (Noda et al, 2015) and acupuncture stimulation at HT7 affects cardiac autonomic neural regulation in healthy individuals, mainly via the PNS (Huang et al, 2015). Acupuncture activates the PNS and default mode network connectivity (Dhond et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Subjects received treatment at HT7 ( Shenmen ) on the dominant hand. HT7 is a commonly used acupuncture point for observing HRV [ 28 , 29 ]. The location of HT7 was determined by using the general guidelines in the World Health Organization Standard Acupuncture Point Locations in the Western Pacific Region [ 30 ].…”
Section: Methodsmentioning
confidence: 99%